Age-Related Functional and Expressional Changes in Efflux Pathways at the Blood-Brain Barrier - Erdő, Franciska; Krajcsi, Péter (Frontiers in Aging Neuroscience, 2019)
During the last decade several papers reported a relationship between advanced age and changes in the integrity of the blood-brain barrier. These alterations manifested not only in the morphology and structure of the cerebral microvessels but also in the expression and function of the transporter proteins in the apical and basolateral surface of the capillary endothelial cells. Age-associated downregulation of the efflux pumps (ABC transporters) resulted in increased permeability and greater brain exposure to different xenobiotics enhancing the risk of drug-induced toxicity. In age-related neurodegenerative pathologies like Alzheimer’s disease the amyloid beta clearance decreased due to P-glycoprotein dysfunction leading to higher brain exposure. In the contrary, in stroke an enhanced P-glycoprotein function was reported in the cerebral capillaries making even more difficult to perform effective neuroprotective therapy in the infarcted brain area. This article is focusing on the role of efflux transporters at the blood-brain barrier in age-related brain pathologies and also in healthy aging.